2015
DOI: 10.15386/cjmed-377
|View full text |Cite
|
Sign up to set email alerts
|

The importance of ubiquitin E3 ligases, SCF and APC/C, in human cancers

Abstract: A normal evolution of the cell-cycle phases consists of multiple consecutive events, which makes it a highly complex process. Its preservation is regulated by Cyclin-Cdks (cyclin-dependent kinases) interactions and protein degradation, which is often controlled by the ubiquitin-mediated proteolysis.The goal of this review is to emphasize the most important features of the regulation of the cell-cycle involved in cancerogenesis, by presenting the involvement of E3 ubiquitin ligases SCF (Skp1-Cul1-F-box protein)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
(140 reference statements)
0
10
0
2
Order By: Relevance
“…The basis of these capabilities is genetic instability and chronic inflammation (14). The E2F family is downstream of CDK-Rb-E2Fs in a cell cycle regulation network (15), and is a crutial transcriptional regulatory factor in the cell cycle. It has been reported that they not only play an important role in cell proliferation and maintain gene stability (13), but also have critical effects on apoptosis, metabolism, differentiation, DNA damage and repair, angiogenesis and so on (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…The basis of these capabilities is genetic instability and chronic inflammation (14). The E2F family is downstream of CDK-Rb-E2Fs in a cell cycle regulation network (15), and is a crutial transcriptional regulatory factor in the cell cycle. It has been reported that they not only play an important role in cell proliferation and maintain gene stability (13), but also have critical effects on apoptosis, metabolism, differentiation, DNA damage and repair, angiogenesis and so on (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…The basis of these capabilities is genetic instability and chronic in ammation [18]. The E2F family is downstream of CDK-E2Fs-Rbnetwork in a cell cycle regulation network [19,20], and is a crucial transcriptional regulatory factor in the cell cycle. It has been reported that they not only play an important role in cell proliferation and maintain gene stability [17], but also have critical effects on apoptosis, metabolism, differentiation, DNA damage and repair, angiogenesis and so on [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Нарушение процессов убиквитинзависимого протеолиза и деградации лизина наблюдается при многих злокачественных заболеваниях. В частности, посредством убиквитинпротеосомной системы осуществляется регуляция на уровне белков модуляторов клеточного цикла -циклинзависимых киназ и p53 [11]. В целом стоит отметить, что сигнальные механизмы, изменения которых выявлены посредством биоинформационного анализа в меланоме, известны как играющие роль в меланомогенезе, что в свою очередь свидетельствует об адекватности исследования, проводимого на основе микрочипирования.…”
Section: Discussionunclassified